KUALITAS BELANJA DAERAH DAN HUBUNGANNYA DENGAN KINERJA PEMBANGUNAN DI PROVINSI BANTEN - Sri Wahyuni; Bambang Juanda; Idqan Fahmi (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2017)
This study aims to analyze the relevant indicators of spending quality in measuring the quality of regional spending as well as the relationship between the quality of regional spending and the development performance of the regencies/cities of Banten Province. This study uses secondary data from the governance, financial and performance development of the districts/cities of Banten Province between 2009 – 2013. The Data are analyzed using Partial Least Squares Structural Equation Model (PLS–SEM) using SmartPLS software version 2.0 & SmartPLS version 3.0. The Results show that there are 21 indicators out of 40 indicators that are relevant in measuring the quality of the districts/cities spending in Banten Province. The change of the spending quality map from 2009 to 2013 shows that the quality of North Banten (Tangerang Regency, Tangerang City, Tangerang Selatan, Serang Regency, Serang City and Cilegon City) is better than South Banten (Pandeglang and Lebak). In addition, the estimation results from the model used indicate that the quality of the region spending of Banten Provinve has a positive relationship with the performance of development with the value of the indicator 0,678. Keywords : Development Performance, PLS-SEM, Spending Quality